The human microbiota: a double-edged sword against the ‘Sword of Damocles’ in PDAC diagnosis and therapy - Sindaco, Maria; Mercanti, Leonardo; Puca, Valentina; Mazzone, Mariangela; Di Marcantonio, Maria Carmela; Muraro, Raffaella; Fiordaliso, Michele; Mincione, Gabriella (Frontiers in Oncology, 2025)
Pancreatic Ductal Adenocarcinoma (PDAC) is currently a major oncological threat given the very low 5-year survival rates of 8-9%. The tumor itself is intertwined with its surrounding tissue in a peculiar tumoral microenvironment (TME) which contributes to resistance against the host immune system and traditional clinical treatments, such as chemotherapy. One of the components of TME is the microbiota, which mainly includes the bacterial species identified in the tumor tissue at various stages. Current literature highlights an active role of the microbiota in tumorigenesis, progression, metastasis, and chemotherapy response in PDAC patients. This review gathered the most recent findings about microbial composition in PDAC patients, along with the effects of intra and extra-tumoral (GI and oral) microbial species on the TME and immune system, their role in tumor progression and immuno-modulation. This paper provides an insight on the potential use of microbes as diagnostic and prognostic markers, and as an additional therapeutic strategy. The study of microbiota offer new ways to slow down carcinogenesis, modulate the immune response, and even serve as an early diagnostic tool in the absence of specific serum markers. In the current review we will offer an inquiry on these potential roles. We sorted out the most recent literature with a comprehensive and critical approach, sourcing papers from PubMed. We exclusively opted for papers that were published in the last 5 years on journals with IF≥4, with a focus on the impact of intra-tumoral microbiome on the natural history of PDAC, from pre-tumoral lesions to metastasis.